Case Report: Squamous Cell Carcinoma of Pancreas With High PD-L1 Expression: A Rare Presentation - Yang, Baohong; Ren, Haipeng; Yu, Guohua (Frontiers in Oncology, 2021)
Primary pancreatic squamous cell carcinoma is sporadic. The diagnosis is usually made following surgery or needle biopsy and requires a thorough workup to exclude metastatic squamous cell carcinoma. Squamous cell carcinoma of the pancreas often has a very poor prognosis. There is no treatment guideline for this type of cancer, and to date, no therapeutic regimen has been proven effective. Here, we report the effectiveness of immunotherapy in combination with chemotherapy against locally advanced squamous cell carcinoma of the pancreas with high programmed cell death ligand 1 (PD-L1) expression. Regional intra-arterial infusion chemotherapy consisting of nab-Paclitaxel followed by gemcitabine infused via gastroduodenal artery every three weeks for two cycles. This therapy resulted in the depletion of carcinoma, and the patient continues to lead a high-quality life with no symptoms for more than 16 months.